Reproductive output of the spider crab Epialtus bituberculatus (H. Milne Edwards, 1834) (Crustacea, Decapoda, Brachyura) associated with beds of the alga Sargassum cymosum (C. Agardh, 1820) on the southeastern Brazilian coast - Cobo, Valter Jose; Barros, Samara de P. [UNESP] (Int Science Services/balaban Publishers, 2009)
The reproductive output of the spider crab Epialtus bituberculatus, which is associated with beds of the alga Sargassum cymosum, was evaluated. Collections were carried out monthly from January through December 2001 in the intertidal of two beaches (Grande and Domingas Dias) on the subtropical southeastern Brazilian coast. The carapace width of ovigerous females was measured and their eggs were counted. A subsample of five eggs was taken from each batch and their volume measured and the stage of embryonic development identified. The fecundity index (FI), and reproductive intensity index (RII), were estimated. In total, 281 ovigerous females were obtained, 108 and 173 from Grande and Domingas Dias beaches, respectively. The egg production was a function of the size of the crabs. The fecundity was significantly different between the two sites. Individuals from the Domingas Dias beach population had a larger average fecundity and greater peaks of RII in comparison to the crabs at Grande beach. Significant differences in egg volume were detected between early and late embryonic stages, at both beaches. The general trend for the egg-production strategy of E. bituberculatus follows the pattern for tropical and subtropical brachyuran species, increasing with body-size. The differences recorded in the present study might be caused by environmental factors such as hydrodynamics, which are quite different between the two beaches, suggesting that this may have importance in the determining the reproductive output of this species.
Keywords: Realized fecundity; egg production; reproductive intensity; Epialtidae